A New Routing Protocols for Reducing Path Loss in Wireless Body Area Network (WBAN) - Al_Barazanchi, Israa; Shibghatullah, Abdul Samad; Selamat, Siti Rahayu (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
In view of the ever-aging society, recent developments in the field of electronics and telecommunications have witnessed the interest in developing an integrated circuit of enhanced surveillance sensors that can be worn and have an ease of movement to monitor vital signs. The main tasks of these electronic devices are collecting physiological information from the patient’s body, sending the information to the medical center via a secure way and ensuring the arrival of this information in a reliable way without any loss of data. This paper proposed a protocol in Wireless Body Area Network (WBAN) to solve the problem of path loss in WBAN. For this purpose, we depend on three sets of scenario applied in OMNET++ environment. The results of proposed solution were compared with RSS path loss factor using three delay and data rate parameters.